Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0024215
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin

Abstract: The cyclosporin family of secondary metabolites isolated from the fungus Tolypocladium inflatum is characterised by a cyclopeptide structure consisting of an 11‐membered amino acid ring, containing N ‐methylated peptide bonds. Parent cyclosporin A (CsA) is a drug widely used to prevent and treat rejection episodes after organ transplantation and can be used in autoimmune diseases. It is immunosuppressive, anti‐inflammatory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Cyclosporin A (CsA) is a long-established clinically important immunosuppressant used routinely since the early 1980s to prevent rejection and graft-versus-host disease in bone marrow and solid organ transplantation (e.g. kidney, heart, and liver) [2]. CsA is a welltolerated and widely used medicine, now also employed in dermatology for treating recalcitrant plague psoriasis, eczema, and atopic dermatitis, and even in ophthalmology for the management of dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclosporin A (CsA) is a long-established clinically important immunosuppressant used routinely since the early 1980s to prevent rejection and graft-versus-host disease in bone marrow and solid organ transplantation (e.g. kidney, heart, and liver) [2]. CsA is a welltolerated and widely used medicine, now also employed in dermatology for treating recalcitrant plague psoriasis, eczema, and atopic dermatitis, and even in ophthalmology for the management of dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A (CsA) is a cyclic undecapepetide originally isolated from the fungus Tolypocladium inflatum [1][2][3]. Although CsA does not bind DNA directly, we and others have found that it causes DNA breakage and genome instability under certain circumstances [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%